АХБОРОТ ТЕХНОЛОГИЯЛАРИ ЙЎНАЛИШИ БЎЙИЧА ИҚТИДОРЛИ ТАЛАБАЛАРНИ ТАНЛАШ ВА ЎҚУВ-БИЛИШ ФАОЛИЯТИНИ ТАШКИЛ ЭТИШ МУАММОЛАРИ - Делов, Т.Э. (SCIENCE and SOCIETY, 2018)
The article describes the intellectual potential of talented students in selected areas, the responsibility of professors and teachers for their spiritual development and their friendly relations with the younger generation, which creates the basis for reaching the higher peaks by young people. It is also stressed that the innovative international experience is the basis for quick and easy access to positive results. The current problems of identifying talented students in the field of ICT are also mentioned by the author.
Keywords: gifted students; student support; educational process; pedagogical assistance; pedagogical technologies; psychological and individual qualities; international experience; talented student in the field of information technologies